1994
DOI: 10.1557/jmr.1994.1566
|View full text |Cite
|
Sign up to set email alerts
|

TEM study of the structure and chemistry of a diamond/silicon interface

Abstract: The interface between diamond and silicon, fabricated by growing diamond films on (001) silicon by microwave plasma assisted chemical vapor deposition (MPACVD), was characterized by high-resolution transmission electron microscopy (HRTEM) and electron energy loss spectroscopy (EELS). Two types of interface morphology were identified. Type A interfaces contain an amorphous transition layer composed of silicon, carbon, and oxygen; the diamond overgrowth on this layer consists of nanocrystalline grains with rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…TEM study of the structure and chemistry of a diamond/silicon interface showed the evidence of b-SiC [17].…”
Section: In Situ Reactionmentioning
confidence: 99%
“…TEM study of the structure and chemistry of a diamond/silicon interface showed the evidence of b-SiC [17].…”
Section: In Situ Reactionmentioning
confidence: 99%
“…Assuming randomly distributed micro-cracks, the damage parameter, D, is related to the crack density by the following expression [13]:…”
Section: Theoretical Model For Degradation Of Thermal Conductivitymentioning
confidence: 99%
“…The ratio of the degraded value of Poisson's ratio (ν) to its intact value (ν 0 ) is also related to the crack density. For practical values of ν ranging from 0 to 0.5, ν ν 0 can be related to C d according to the following expression [13]:…”
Section: Theoretical Model For Degradation Of Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to be sensitive to details of the biasing pretreatment and growth procedures. Under certain circumstances, one finds cubic or (3C-͒ SiC formation, 4,5 amorphous carbon, 6 and nanocrystalline graphite 7 at the interface, or at least in part of the interface. SiC formation has also been observed in diamond deposition on Si without bias enhancement.…”
Section: Introductionmentioning
confidence: 99%